P-STAT3 Inhibition Activates Endoplasmic Reticulum Stress-Induced Splenocyte Apoptosis in Chronic Stress - Song, Manyu; Wang, Chaoran; Yang, Haotian; Chen, Yongping; Feng, Xiujing; Li, Bei; Fan, Honggang (Frontiers in Physiology, 2020)
Chronic stress leads to immunosuppression and induces splenocyte apoptosis. STAT3 is a transcription factor that regulates immunity and apoptosis; however, it is unclear whether the increased expression of phosphorylated STAT3 (p-STAT3) observed in chronic stress is related to splenocyte apoptosis. To explore the relationship between splenocyte apoptosis and STAT3 in chronic stress, we treated rats undergoing a 21-day chronic restraint stress program with the STAT3 inhibitor S3I-201. This chronic stress model was verified by observing rats’ behavior and measuring their serum corticosterone levels. Chronic stress led to increased expression of anti-inflammatory cytokines, and p-STAT3 inhibition enhanced splenocyte apoptosis in chronic stress. We detected key proteins in three apoptotic pathways to determine which pathway mediated increasing splenocyte apoptosis, and found that the death receptor pathway was the main apoptotic pathway that occurred in the spleen during chronic stress. The unfolded protein response (UPR) was also activated, but the Bcl-2 family was not involved in chronic stress. P-STAT3 inhibition had no influence on the Bcl-2 family and the death receptor pathway; however, p-STAT3 inhibition disrupted the pro-survival function of the UPR by decreasing the expression of ATF6α and p-IRE1α. Furthermore, p-STAT3 inhibition activated ER stress by promoting the expression of CHOP, p-JNK, and procaspase-12. Collectively, these findings indicate that the increased p-STAT3 expression during chronic stress may promote splenocyte survival by activating the UPR. Consequently, STAT3 and the UPR may be considered as potential therapeutic targets for chronic stress in the future.